Full-field strain mapping of healthy and pathological mouse aortas using stereo digital image correlation. (May 2023) - Lane, Brooks A.; Cardoza, Ricardo J.; Lessner, Susan M.; Vyavahare, Narendra R.; Sutton, Michael A.; Eberth, John F.
Abstract: The murine aorta is a complex, heterogeneous structure that undergoes large and sometimes asymmetrical deformations under loading. For analytical convenience, mechanical behavior is predominantly described using global quantities that fail to capture critical local information essential to elucidating aortopathic processes. Here, in our methodological study, we used stereo digital image correlation (StereoDIC) to measure the strain profiles of speckle-patterned healthy and elastase-infused, pathological mouse aortas submerged in a temperature-controlled liquid medium. Our unique device rotates two 15-degree stereo-angle cameras that gather sequential digital images while simultaneously performing conventional biaxial pressure-diameter and force-length testing. A StereoDIC Variable Ray Origin (VRO) camera system model is employed to correct for high-magnification image refraction through hydrating physiological media. The resultant Green-Lagrange surface strain tensor was quantified at different blood vessel inflation pressures, axial extension ratios, and after aneurysm-initiating elastase exposure. Quantified results capture large, heterogeneous, inflation-related, circumferential strains that are drastically reduced in elastase-infused tissues. Shear strains, however, were very small on the tissue's surface. Spatially averaged StereoDIC-based strains were generally more detailed than those determined using conventional edge detection techniques.